Studi Pendahuluan: Strategi Promosi Kesehatan Mental Di Lingkungan Kampus Melalui Partisipasi Dosen Wali - Ni Gusti Made Rai; Tony Dwi Susanto; Eka Dian Savitri; Aurelius Ratu (Institut Teknologi Sepuluh Nopember, 2020)
In providing qualified, physically, and mentally health graduates, students'mental health should be paid more attention than before. As the mentalhealth affects a person's psychological condition, in this preliminaryresearch, we seek to formulate the strategy in giving a framework for thePDC program. Academic advisors (dosen wali) became participants in thisstudy. We consider them to know better what students need and can realizean effort to prevent mental health problems. The research used qualitativedata and the FGD method to gain the data. The results indicated that howacademic advisors need student mental health service as part of the academicprocess, which showed the crucial issues related to college student mentalhealth.